2022
DOI: 10.1007/s00410-022-01936-3
|View full text |Cite
|
Sign up to set email alerts
|

Newly detected shock-induced high-pressure phases formed in amphibolite clasts of the suevite breccia (Ries impact crater, Germany): Liebermannite, kokchetavite, and other ultrahigh-pressure phases

Abstract: Amphibolite clasts in the suevite of the Ries impact crater contain shock-induced melt veins (SMVs) with high-pressure phases such as majoritic garnet, jadeitic clinopyroxene and others. In addition, heat conduction from hot SMVs into adjacent rock portions locally produced further high P–T melt pools. These melts were preferentially generated in rock domains, where the SMVs cross older (‘pre-Ries’) veinlets with analcime or prehnite and larger grains of sericitized plagioclase. Melting of such chemically diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…New findings of kokchetavite in polyphase inclusions are being reported from a growing number of localities 7–9,14 . Surprisingly, almost all of these findings occur in rocks with low bulk potassium content.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…New findings of kokchetavite in polyphase inclusions are being reported from a growing number of localities 7–9,14 . Surprisingly, almost all of these findings occur in rocks with low bulk potassium content.…”
Section: Resultsmentioning
confidence: 95%
“…Surprisingly, almost all of these findings occur in rocks with low bulk potassium content. The common interpretation for the origin of kokchetavite is that it comprises a part of the crystallization products of the melt captured at high or even ultrahigh‐pressure conditions 4–6,8,13–16 . This raises the question of the possible origin of this unusual phase in rocks with relatively low potassium concentration 3,8,9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More findings of kumdykolite and/or kokchetavite have been reported recently, such as multiphase inclusions with kokchetavite in detrital garnet from UHP metamorphic terrane in eastern Papua New Guinea (Baldwin et al, 2021) and kumdykolite and kokchetavite in multiphase inclusions (together with cristobalite) in garnets from UHP terrains in the central Saxonian Erzgebirge in the northwestern Bohemian Massif in Germany (Schönig et al, 2020). Stähle et al (2022) reported the finding of kokchetavite, together with some other UHP phases, in alkali-rich melt glass (shock-induced melt veins) in weakly to moderately shocked amphibolite clasts from the young Ries impact crater in southern Germany (age of structure: 14.8 Ma). Here kokchetavite is found to be in an association with other UHP minerals (liebermannite, albitic jadeite and the immediate vicinity of majoritic garnet), which may indicate crystallisation pressures of nearly 10 GPa.…”
Section: Kumdykolite and Kokchetavitementioning
confidence: 81%